Evaluation of physical fitness after attachment of neuropriming device among adolescent football players - Mustafa, Mohammad Saifatullizam (2022)
Transcranial direct current stimulation (tDCS) is a newly developed, noninvasive technique that can help researchers understand the relationship between brain processes and exercise performance. The purpose of this study was to examine the effect of tDCS on health-related fitness and skill-related fitness tests among adolescent Malaysian football players of various age groups. The study employed a blinded crossover, randomised controlled trial, to compare the non-invasive approach to a shamcondition. Sixty-one healthy male football players from the Malaysian National Football Development Programme (NFDP), aged between 13 to 17 years old, with at least two years of competitive experience representing their state, volunteered to take part in this study. The participants’ anthropometric assessments were measured, including their weight, height, and body mass index (BMI). The participants were randomised to either receive tDCS or sham stimulation conditions, with 14 days apart. The health-related fitness assessment included of bleep test for VO2 max, body composition, back and leg strength, hand grip strength, one-minute sit-up and push up tests and sit and reach for flexibility. Skill-related fitness assessments consisted of agility test, standing long jump, vertical jump, force platform and 30-meter sprint were measured, with 10 to 15 minutes of rest in-between testing. The results from the paired t-test showed that the football players who received tDCS stimulation improved in their back and leg strength test, one-minute sit up, right handgrip strength test, vertical jump test and force platform when compared to sham condition. However, only VO2 max, right handgrip strength test and 30-meter sprint test showed a significant improvement using the tDCS stimulation, with p = 0.021, p = 0.004 and p = 0.044 respectively. Repeated measure analysis of variance (ANOVA) within groups analysis showed significance improvement using the tDCS stimulation in VO2 max for group under 13, handgrip strength test for group under 15, and vertical jump and agility test for group under 17. Improvement of test were shown for back and leg strength test, one-min sit up, one-min push up, agility test and vertical jump for group under 13; handgrip test, standing long jump, vertical jump, one-min sit up and force platform for group under 15; VO2 max, right handgrip test, flexibility, one-min sit up, vertical jump and force platform for group under 17. The results demonstrated that tDCS improved some health-related fitness and skill-related fitness measurements in the Malaysian adolescents’ football players. The study added to the literature that neurostimulation technology has a positive relationship between the brain and physical performance. The findings are hoped to be applied and aid in the development of specific training programmes for Malaysian football players to achieve peak performance. However, more research is needed to determine the long-term effects of this intervention on training as well as the precise mechanism through Halo Sports.